Identification of miRNA Signature Associated With Erectile Dysfunction in Type 2 Diabetes Mellitus by Support Vector Machine-Recursive Feature Elimination - Xu, Haibo; Zhao, Baoyin; Zhong, Wei; Teng, Peng; Qiao, Hong (Frontiers in Genetics, 2021)
Diabetic erectile dysfunction (DMED) is one of the most common complications of diabetes mellitus (DM), which seriously affects the self-esteem and quality of life of diabetics. MicroRNAs (miRNAs) are endogenous non-coding RNAs whose expression levels can affect multiple cellular processes. Many pieces of study have demonstrated that miRNA plays a role in the occurrence and development of DMED. However, the exact mechanism of this process is unclear. Hence, we apply miRNA sequencing from blood samples of 10 DMED patients and 10 DM controls to study the mechanism of miRNAs action on DMED. Firstly, we found four characteristic miRNAs as signature by the SVM-RFE method (hsa-let-7E-5p, hsa-miR-30d-5p, hsa-miR-199b-5p, and hsa-miR-342-3p), called DMEDSig-4. Subsequently, we correlated DMEDSig-4 with clinical factors and further verified the ability of these miRNAs to classify samples. Then, we obtained the target mRNAs of DMEDSig-4 and studied the miRNA-mRNA interaction. Finally, we conducted functional enrichment analysis of DMEDSig-4 target mRNAs and constructed the functional network. In brief, our work proposed that DMEDSig-4 had a significant association with DMED and had a superior classification effect. Meanwhile, the DMEDSig-4 could help in the development of new therapies for DMED.